Rancang Bangun Sistem Transmisi Poros Pisau Penghancur Pada Mesin Crusher Plastik High Density Polyethylene (HDPE) - Pramudi, Ganjar; Nur Rohman, Farhan (Jurnal Teknik Mesin Indonesia, 2025)
The amount of plastic waste continues to rise alongside the increasing use of plastic packaging products. To mitigate the plastic problem in Indonesia, one approach is to recycle HDPE plastic waste into powder that can be utilized for composite materials. The initial step in producing powder from HDPE plastic waste involves shredding the HDPE plastic into small flakes. These plastic flakes are then ground into fine powder. The HDPE plastic crusher machine is powered by a 3 HP electric motor and operates at a rotational speed of 1400 rpm. The design of the blades on this machine features sharp and wide edges, with a total of eight blades. Additionally, the machine body is designed with a wider shape to optimize the plastic crushing process. The transmission system used to transfer rotation consists of a pulley, V-belt, and shaft. Proper planning of the shaft is essential to determine the appropriate diameter for the HDPE plastic crusher machine. Based on the planning results, the shaft diameter selected is 25 mm, with a minimum required diameter of 16.24 mm. The final rotational speed of the crusher blade shaft is 2800 rpm, with a torque of 13,410 N·mm applied to the shaft.